Music, Memory and Narrative: The Art of Telling in Tale of Tales. (November 2022) - Cross, Ian
Skazka Skazok/Tale of Tales (Yuri Norstein, 1979) has delighted and puzzled audiences and critics ever since its release. It presents a series of beautifully-animated episodes that seem to make narrative sense at the micro-level and that appear to fit together as a whole, but leaves the audience bemused as to why this should be so. The article discusses the history and context of the film, arguing that the ways in which sound and, particularly, music are deployed in relation to its visual elements provide powerful clues and cues as to the film's over-arching narrative significances. Close analysis of the film's music, sound and visuals reveals teleological underpinnings that are realized by means of alignment and re-alignment of music and image, leading to a new understanding of how the film and its success can be interpreted.